The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/eea.12205
|View full text |Cite
|
Sign up to set email alerts
|

Sirex noctilio flight behavior: toward improving current monitoring techniques

Abstract: Sirex noctilio Fabricius (Hymenoptera: Siricidae), an invasive woodwasp from Spain and North Africa, has an expanding global presence in pine forests. Although their populations are managed in most parts of the world, the success rate of existing prevention and control strategies has been historically variable, and there is consensus that monitoring techniques could be improved with increased knowledge about the behavioral biology of this insect. We conducted descriptive field studies in pine plantations in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Our study of the take-off behaviour of C. medinalis showed that the take-off percentage of young female moths was higher than that of young male moths and that female moths were more likely to take off than male moths, which may indicate more frequent emigration behaviour of female moths than male moths. In addition, because females need to find food and oviposition sites, they usually have strong flight capabilities 42 . Our results indicated that in C. medinalis , females have stronger flight capability than males; this pattern is common among other insects, such as Lygus lineolaris 43 , Tetraopes tetrophthalmus 44 , Culex pipiens pallens 45 and Mamestra brassicae 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study of the take-off behaviour of C. medinalis showed that the take-off percentage of young female moths was higher than that of young male moths and that female moths were more likely to take off than male moths, which may indicate more frequent emigration behaviour of female moths than male moths. In addition, because females need to find food and oviposition sites, they usually have strong flight capabilities 42 . Our results indicated that in C. medinalis , females have stronger flight capability than males; this pattern is common among other insects, such as Lygus lineolaris 43 , Tetraopes tetrophthalmus 44 , Culex pipiens pallens 45 and Mamestra brassicae 46 .…”
Section: Discussionmentioning
confidence: 99%
“…α and β pinenes in a ratio of 70 : 30, respectively) are used to sample and monitor female wasp populations in affected areas (Bashford ; Martínez et al. ). Regardless of these findings, to date the most commonly used way to monitor wasp populations when in low densities is the use of girdled or herbicide‐treated pines as a lure, which are costly and logistically difficult to implement (Zylstra et al.…”
Section: Introductionmentioning
confidence: 99%
“…Even though S. noctilio seemed adept at disseminating its population because of flight capacity, the result demonstrates that it still is difficult for a single S. noctilio adult to widely proliferate by itself. Recent field studies suggest that S. noctilio dispersal within a forest is very limited, less than 150 meters [12,13]. Given these constraints, the best strategy for S. noctilio seems to be to alight in a nearby tree and use its final resources for ovipositional activity [14].…”
Section: Discussionmentioning
confidence: 99%